Factors affecting the stability of maxillary extraction site closure - Larissa BRESSANE; Guilherme JANSON; Rodrigo NAVEDA; Marcos Roberto de FREITAS; Daniela GARIB (Dental Press Editora, 2021)
ABSTRACT Introduction: A side effect observed in cases treated with extractions is the instability of orthodontic space closure. Objective: The aim of this study was to investigate the influence of gingival invagination, presence of third molars and facial pattern, on the stability of orthodontic space-closure in the maxillary arch. Methods: Ninety-nine subjects (41 male and 58 female) with Class I malocclusion treated with four premolars extraction were evaluated. Extraction sites reopening and gingival invaginations were evaluated in scanned dental models in the posttreatment and 1-year posttreatment stages (mean age 16.1 years). Third molars presence was evaluated at 1-year posttreatment panoramic radiographs, and the facial pattern (SN.GoGn) was evaluated in the initial lateral headfilms. Multiple logistic regression analysis was used to estimate the influence of the aforementioned independent variables on the frequency of extraction space reopening. Results: Space reopening was observed in 20.20% of the subjects 1-year post-debonding. Gingival invaginations were present in 25.73% of quadrants after debonding and in 22.80% 1-year posttreatment. The mean pre-treatment SN.GoGn was 35.64 degrees (SD=5.26). No significant influence was observed of the three independent variables on the instability of extraction site closure. Conclusions: The presence of gingival invaginations, third molars and facial growth pattern do not seem to influence maxillary extraction sites reopening.